Reflections on data network technology - Lintao JIANG (Dianxin kexue)
The history of data network development and standardization was reviewed,and the idea ofsub-generational development concept for future network was put forward.It was pointed out that there were two technical routes in network design:the development technology route with users and business applications as the core,the gradual increase of network capabilities according to the needs of users and applications,and the development technology route with network as the core and the main body of capacity responsibility.Network 5.0 adopts “network as the core design concept”.A detailed description of three important capabilities of network 5.0 was given:endogenous credibility and security,endogenous network resource perception,deployment and control,and endogenous network certainty.